Hydroxychloroquine- A Saviour from The Past - A Review - DESAI, KARISHMA; ARIVARASU, LAKSHMINARAYANAN; RANI. S, LESLIE (The journal of contemporary issues in business and government, 2020)
Hydroxychloroquine is a widely used anti-malarial drug that has been under study for its effect against coronavirus. It has a wide range of applications for various reasons. It also causes certain side effects in the human body when consumed for long. HCQ has been a proven treatment plant for autoimmune disorders like rheumatoid arthritis and SLE. Hydroxychloroquine is a widely used anti-malarial drug. It possesses various benefits and is also used in autoimmune disorders like lupus and rheumatoid arthritis. Hydroxychloroquine sulfate is known to be a derivative of Chloroquine. In this review, we aim to analyze the properties of HCQ, know about the side effects and understand its role in treating COVID-19 and summarize our observations. A systematic search strategy was employed and articles were found using keywords. Literature was taken from databases like PubMed and Google Scholar. Articles that discussed the use of HCQ in COVID-19 were included. Other articles which had data regarding HCQ- side effects, structure and its applications were also included. A total of about 70 articles were collected initially. Multiple articles were added later from other sources. After eliminating articles that did not meet the inclusion criteria, more than 30 studies were finally obtained. This review summarized the use of HCQ in COVID-19. Its structure, and other roles in treatment of Autoimmune disorders were also discussed in detail.